Ruptured alliances: Prosecutorial lobbying, victims’ interests and punishment policy in Illinois - Degenshein, Anya (Punishment & society, 2023)
Using a combination of FOIA-requested legislative committee hearings and in-depth interviews, this manuscript investigates the work of Illinois prosecutorial lobbyists in state-level crime policy during a time of penal reform. I find that prosecutorial lobbyists are a regular and influential presence in policy discussions, advocating primarily for 'law and order' policies that expand prosecutorial discretion, even following the Great Recession. I also find that they repeatedly evoke their relationship to crime victims to frame their policy positions for a bipartisan audience. However, attention to discourse reveals that victims’ own interests regularly clash with prosecutorial discretion. These clashes create what I term discursive ruptures, or uncomfortable and surprising rhetorical fissures that emerge in what is otherwise seen as a near iron-clad political alliance. In such instances, prosecutors risk alienating a key source of their political legitimacy to protect their own discretionary authority. Beyond insight into momentary political discomfort, these ruptures suggest that the powerful and productive alliance between prosecutors and victims is neither as natural nor as robust as relational perspectives have generally assumed, unearthing fault lines in prosecutors’ unparalleled power to punish.